Resistência mecânica do solo ao tráfego de pneus radiais em função da relação peso/potência do trator - Alcântara, Aline Spaggiari [UNESP] (2017)
The factors that most influence the yield of traction are soil conditions, tire size, weight / power relationship, and tire type (radial / diagonal). The use of specific tires for a certain type of rolling surface would increase their operational performance. Therefore, the characterization of the tire, use of the required load on the wheel associated with soil compaction studies, may indicate better working conditions and consequently reduced fuel consumption. The objective of this study was to evaluate the mechanical resistance to soil penetration, the area mobilized by the tires and the fuel consumption after traffic of two types of rear (710 / 70R38 and 650 / 85R38) and front (600 / 70R28 and 600 / 65R28) combined with four tractor weight / power relationship in an area prepared for sugarcane cultivation. The statistical design was a factorial with randomized blocks subdivided with four replicates, statistical analysis was performed by the F test and when significant the Tukey test was performed at 5% probability, for the interactions between treatments regression adjustment of higher exponent that presented significance and Maps to better explain the behavior of the variable. Tires and weight / power relationship did not interfere in the mechanical resistance of the soil to penetration in the present work. Soil compaction increases as the number of passes increases, giving the soil greater mechanical resistance to penetration, negatively interfering with layer 10 to 20 cm. The isoline maps indicated soil penetration resistance points, which although not critical, show the importance of the adequacy of the tractors and their equipment in the reduction of soil compaction for better development of the crop to be implanted.